2019
DOI: 10.1038/s41598-019-48291-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-based functional studies reveal that galectin-3 plays a protective role in the pathogenesis of intestinal Behçet’s disease

Abstract: The pathogenesis of intestinal Behçet’s disease (BD) remains poorly understood. Therefore, we aimed to discover and validate biomarkers using proteomics analysis and subsequent functional studies. After two-dimensional electrophoresis, candidate proteins were identified using matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometry (MALDI-TOF/TOF MS). We validated these results by evaluating the protein levels and their functions in vitro using HT-29 colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Acetate is known to attenuate inflammasome activation ( 60 ). Increased inflammasome expression has been reported in BD patients with skin manifestations ( 61 ) and BD patients with intestinal problems ( 62 ). B. vulgatus attenuated atherosclerosis through Foxp3 upregulation and TNFα downregulation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acetate is known to attenuate inflammasome activation ( 60 ). Increased inflammasome expression has been reported in BD patients with skin manifestations ( 61 ) and BD patients with intestinal problems ( 62 ). B. vulgatus attenuated atherosclerosis through Foxp3 upregulation and TNFα downregulation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 is a 31-kDa chimeric lectin involved in the pathophysiological processes of a variety of cells (29,39). It has become a biomarker for cardiovascular diseases such as heart failure (41), aortic stenosis (15), and myocardial aging (26).…”
Section: Discussionmentioning
confidence: 99%
“…There was no correlation between HSPA6 expression levels and oral ulcers, genital ulcers, or disease activity among Crohn’s disease patients. 65 Additionally, Lee et al 66 found increased HSP27 and decreased HSP60 protein expression levels in 17 BS patients compared to 17 healthy controls, using two-dimensional (2D) electrophoresis and MALDI-TOF/TOF MS methods.…”
Section: Heat Shock Proteins In Behçet Syndromementioning
confidence: 99%